Ordinal scale and statistics in medical research. Issue 6519 (22nd February 1986) - Forrest, M; Andersen, B
Abstract : A survey of the 1982 editions of 12 medical journals showed that in at least 70% of 175 papers employing ordinal measurement scales, statistical methods were used, which do, in fact, assume a more refined measurement scale. Non-parametric methods suited for analysis of ordinal data are listed.